The neonicotinoid electronegative pharmacophore plays the crucial role in the high affinity and selectivity for the Drosophila nicotinic receptor: an anomaly for the nicotinoid cation-? interaction model. - Tomizawa, M.; Zhang, N.; Durkin, K.A.; Olmstead, M.M.; Casida, J.E. (Biochemistry, 2003)
Cation-pi interaction, a prominent feature in agonist recognition by neurotransmitter-gated ion channels, does not apply to the anomalous action of neonicotinoids at the insect nicotinic acetylcholine receptor (nAChR). Insect-selective neonicotinoids have an electronegative pharmacophore (tip) in place of the ammonium or iminium cation of the vertebrate-selective nicotinoids, suggesting topological divergence of the agonist-binding sites in insect and vertebrate nAChRs. This study defines the molecular and electronic basis for the potent and selective interaction of the neonicotinoid electronegative pharmacophore with a unique subsite of the Drosophila but not of the vertebrate alpha4beta2 nAChR. Target site potency and selectivity are retained when the usual neonicotinoid N-nitroimine (=NNO(2)) electronegative tip is replaced with N-nitrosoimine (=NNO) or N-(trifluoroacetyl)imine (=NCOCF(3)) in combination with an imidazolidine, imidazoline, thiazolidine, or thiazoline heterocycle. X-ray crystallography establishes coplanarity between the heterocyclic and imine planes, including the electronegative substituent in the trans configuration. The functional tip is the coplanar oxygen atom of the N-nitrosoimine or the equivalent oxygen of the N-nitroimine. Quantum mechanics in the gas and aqueous phases fully support the conserved coplanarity and projection of the strongly electronegative tip. Further, a bicyclic analogue with a nitro tip in the cis configuration but retaining coplanarity has a high potency, whereas the N-trifluoromethanesulfonylimine (=NSO(2)CF(3)) moiety lacking coplanarity confers very low activity. The coplanar system between the electronegative tip and guanidine-amidine moiety extends the conjugation and facilitates negative charge (delta(-)) flow toward the tip, thereby enhancing interaction with the proposed cationic subsite such as lysine or arginine in the Drosophila nAChR.